Pemetaan dan Penyuluhan Tentang Ketidakmerataan Akses Pendidikan Dasar di Baubau Counseling on Bipolar - Arnis Arnis; Haswah Haswah; Linda Darmayanti; Nashatun Nashatun (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2022)
Basic education is a fundamental right for every child, yet disparities in access to education persist in various regions, including Baubau City, Southeast Sulawesi. This study aims to map the disparities in access to basic education in Baubau and evaluate the outreach efforts undertaken to raise public awareness of the importance of education. The research employs a combination of field surveys, interviews with education stakeholders, and analysis of spatial and demographic data to assess the current situation and the impact of existing interventions.The findings of the research reveal significant disparities in educational access between urban and rural areas, with rural regions facing greater challenges. Key factors influencing these disparities include inadequate infrastructure, a shortage of qualified teachers, and the economic challenges faced by families in remote areas, which limit children's ability to attend school regularly. Furthermore, there is a lack of community awareness regarding the importance of education, which exacerbates the problem.